2018
DOI: 10.1002/2017jc013712
|View full text |Cite
|
Sign up to set email alerts
|

Observed Characteristics and Vertical Structure of Mesoscale Eddies in the Southwest Tropical Pacific

Abstract: In the Southwest Pacific Ocean, waters transit from the subtropical gyre before being redistributed equatorward and poleward. While the mean pathways are known, the contribution to the mixing and transport of the water from mesoscale eddies has not been comprehensively investigated. In this research, satellite altimetry data, combined with an eddy detection and tracking algorithm is used to investigate the distribution and surface characteristics of mesoscale eddies in this region of complex bathymetry (10°S–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 66 publications
(141 reference statements)
5
50
0
1
Order By: Relevance
“…This increases the merging efficiency as well as d m i . The merging distances observed in the HYCOM dataset are reproduced by the idealized simulations on the f-plane: the values of d m i match well the observed d m for all Ro and Bu studied (in particular for simulations with H = 1000 m and α = 2, as expected -in the ocean, eddies are mostly Gaussian 37 , and about 1000 m deep [41][42][43][44] ). With the β-effect, if eddies are not constrained by a disk, d m in the HYCOM dataset is significantly larger than the d m i values observed in idealized simulations, especially for small Bu and Ro.…”
Section: Figuresupporting
confidence: 73%
“…This increases the merging efficiency as well as d m i . The merging distances observed in the HYCOM dataset are reproduced by the idealized simulations on the f-plane: the values of d m i match well the observed d m for all Ro and Bu studied (in particular for simulations with H = 1000 m and α = 2, as expected -in the ocean, eddies are mostly Gaussian 37 , and about 1000 m deep [41][42][43][44] ). With the β-effect, if eddies are not constrained by a disk, d m in the HYCOM dataset is significantly larger than the d m i values observed in idealized simulations, especially for small Bu and Ro.…”
Section: Figuresupporting
confidence: 73%
“…Our results show that the penetrating depth D of eddies in this region is approximately 800 m, which agrees well with the previous authors' conclusions. Based on the salinity and temperature anomalies in the Southwest Pacific Ocean (10°S–30°S, 140°E–190°E), Keppler et al () showed that on average, eddies in these locations are more deep‐reaching than those found toward the north of the study region. Their findings show that the penetrating depth of eddies is between 400 and 1,000 m, and our results are consistent with their findings (Table and Figure a).…”
Section: Resultsmentioning
confidence: 95%
“…In the present study, to investigate the aspect of an eddy, only the T/S profile at the eddy center is needed to calculate the buoyancy frequency N c (see formula (10)). Following Keppler et al () and Sun et al (), all profiles in which a float is trapped inside the eddies (as determined by the altimeter observations) satisfy the following conditions: Argos' position coordinates were transformed into an eddy‐centered polar coordinate system normalized by the eddy radius. Therefore, an Argo float accurately situated at the eddy center will have the coordinates ( Δr = 0), for an Argo float accurately situating at the boundary of an eddy will have coordinates ( Δr = 1).…”
Section: Methods and Datamentioning
confidence: 99%
“…How valid are the seasonal cycles from the gliders in the presence of both eddies and interannual variations, with the irregular and limited temporal distribution of the glider deployments? In terms of eddies, Keppler et al () found that mesoscale eddies west of Vanuatu are numerous and energetic and affect the water properties down to at least 500 m. However, their results also show that along the Queensland boundary, the eddy numbers, radius, amplitude, and EKE are much reduced—their influence on the boundary currents may in fact be quite low. Results from OFAM3.0 using the glider temporal sampling (on the tracks in Figure ) produce seasonal patterns at least qualitatively similar to climatological values (Figure S6).…”
Section: Discussionmentioning
confidence: 99%